Collected essays. Volume I, Reason in action - Finnis, John. (Oxford : Oxford University Press, 2011)
'Reason in Action' collects John Finnis's work on practical reason and moral philosophy. Ranging from foundational issues of meta-ethics to modern ethical debates, the essays trace the emergence and development of Finnis's new classical theory of natural law through close engagement with a broad range of thinkers and problems.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Natural law; Ethics; Practical reason; Law and ethics